What is your vocation? - Eswaran, Vijay, Dato'; Balagtas,Chandravali Dasi; Munian, Maralikrishnan; VStudios ([S.l.] : VStudios, 2008)
A talk by Dato' Vijay Eswaran at Crystal Crown Hotel, Petaling Jaya, Malaysia 2006, V-Malaysia revisited
Title from title screen
V-Malaysia revisited
Executive producer, Pathman Senathirajah
DVD format
Keywords: Multilevel marketing; Direct marketing